Analysis of Student Errors in Solving SPLDV Questions at Suluun Christian High School - Franly Y. Mandagi; Derel F. Kauang; Jorry F. Monoarfa (Journal on Education, 2023)
This research aimed to identify the causes of and solutions for student mistakes when tackling SPLDV problems. Descriptive qualitative research describes this kind of study. Data for this study was gathered using tests, interviews, and direct observation. The topic of a set of linear equations in two variables is put to the "description test." This research describes student errors and the factors that contribute to those errors when solving word problems involving the concepts of the System of Linear Equations in Two Variables (SPLDV). The blunder concerns steps one through four: (1) problem understanding; (2) problem transformation; (3) process skills; and (4) final answer writing.